2012
DOI: 10.1038/nature11084
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystal-mediated self-assembly at nanodroplet interfaces

Abstract: Technological applications of liquid crystals have generally relied on control of molecular orientation at a surface or an interface. Such control has been achieved through topography, chemistry and the adsorption of monolayers or surfactants. The role of the substrate or interface has been to impart order over visible length scales and to confine the liquid crystal in a device. Here, we report results from a computational study of a liquid-crystal-based system in which the opposite is true: the liquid crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 25 publications
1
70
0
Order By: Relevance
“…Past studies from our own groups have shown that LCs confined in small droplets can be used to induce formation of intriguing surfactant nanophases at their interfaces (15). Experiments and simulations have also shown that the defects that arise in LC droplets can be used to localize individual nanoparticles or pairs of nanoparticles with considerable precision (16,17).…”
mentioning
confidence: 99%
“…Past studies from our own groups have shown that LCs confined in small droplets can be used to induce formation of intriguing surfactant nanophases at their interfaces (15). Experiments and simulations have also shown that the defects that arise in LC droplets can be used to localize individual nanoparticles or pairs of nanoparticles with considerable precision (16,17).…”
mentioning
confidence: 99%
“…[3][4][5] For many of these applications, it is essential to generate detailed theoretical and computational predictions of the system's structure and properties as a function of material characteristics, including any interfaces that may be used to control or manipulate the material's behavior. [6][7][8] Liquid crystals exhibit intriguing structural features at multiple lengths scales. Defects, which represent an integral part of the structure, have characteristic dimensions in the range of 10 nm.…”
Section: Introductionmentioning
confidence: 99%
“…One can rely on a) E-mail: depablo@uchicago.edu advanced sampling techniques to identify equilibrium morphologies but, at present, many-body simulations are highly computationally demanding for systems exceeding characteristic dimensions on the order of a hundred nanometers. 7,8,14 An alternative approach consists of adopting a continuum representation of the free energy of the liquid crystal, e.g., in terms of the Landau-de Gennes model, but to resort to a Monte Carlo method to identify the equilibrium (free-energy minima) structure of the system. Such a strategy has been particularly fruitful in the context of ordered polymeric materials, where it is often referred to as theoretically informed coarse grained simulation, [15][16][17][18][19] and in this work, we develop it in the context of liquid crystalline systems.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly can be modulated by the presence of interactive molecules and materials, and these additives can operate as templates leading to regular patterns and specific shapes [131][132][133]. Assemblies within confined media often induce high-level alignment and orientations [134,135] that cannot be obtained in unrestricted media. Application of external forces such as electric fields, magnetic fields, and mechanical flows to self-assembling systems can be used to modify the self-assembly motifs [136][137][138].…”
Section: Future Perspectivesmentioning
confidence: 99%